The use of Cartography of Controversy within socioscientific issues-based education: students’ mapping of the badger-cattle controversy in England - Christodoulou, Andri; Levinson, Ralph; Davies, Paul; Grace, Marcus; Nicholl, Joanne; Rietdijk, Willeke (International Journal of Science Education, 2021)
This qualitative study examines the pedagogical potential that a Cartography of Controversy (CoC) approach has in enabling secondary school students to unravel the complexity of socioscientific issues and to communicate about them. The aim was to examine the types of knowledge and the ways in which students approached uncertainty when asked to explore the badger-cattle controversy in England using the CoC approach. A learning sequence focusing on mapping controversies was designed and implemented across three lessons. Data collected from the students’ cartographies and the audio-recordings of their group discussions during the mapping tasks showed that students were able to use scientific, economic, cultural, social, moral and political types of knowledge in their exploration of the controversy. Identifying tensions between different types of knowledge and becoming aware of their own uncertainties about the issue through posing and recording questions allowed students to identify where uncertainty existed within the SSI explored. The CoC approach allowed affordances for understanding the SSI depending on students’ framing of the task (familiarisation, exploration, consolidation) and on the cartography’s function as an observation, visualisation, and reflection tool at different stages of the learning sequence. Implications for further research and practice for developing students’ socioscientific reasoning are discussed.
Keywords: Socioscientific issues; cartography of controversy; qualitative study; secondary education; socioscientific reasoning